Mathematical Representation of High School Students in Understanding the Concept of Arithmetic Sequences and Series - Irawati, Sri; Hasanah, Sri Indriati; Zayyadi, Moh; Zein, Arifatul Melinda (FKIP Universitas Lampung, 2022)
This study aims to describe the mathematical representation ability of class XI MA Sumber Payung students in understanding the concepts of arithmetic sequences and series. This type of research is descriptive qualitative research. The results obtained by students with high math skills in understanding the concepts of arithmetic sequences and series are in the form of representations of mathematical equations/expressions, where students can create mathematical equations or models from other representations given, solve problems involving mathematical expressions and representations of words/written texts. Students can write down what is known and asked in a data or information, so that in answering questions using words or written text. Likewise for students with low mathematical abilities, representation in understanding the concept of arithmetic sequences and series is in the form of representations of mathematical equations/expressions and representations of words/text.Keywords: Representation, understanding arithmetic concepts, sequences and series.DOI: http://dx.doi.org/10.23960/jpmipa/v23i1.pp78-86